Representasi Lingkungan Hidup dalam Papantung Masyarakat Suku Sangihe di Desa Manente Kecamatan Tahuna Kabupaten Sangihe (Kajian Ekostilistika) - Sarleoki Nancy Umkeketony; Setya Yuwana Sudikan (ELite Journal : International Journal of Education, Language, and Literature, 2019)
Sangihe tribe or known by the tribe Sangir community community that occupies small islands in the District of Sangihe Islands in North Sulawesi Province. The islands that reside in the Sangihe tribe are located between Sulawesi Island and Mindanao Island, which borders the Philippines. In the past the Sangihe tribe did not recognize literature in written form but in oral literature. This study aims to describe Natural representation in sounds of language in Papantung Sangihe Tribe Society in Manente Village, Tahuna Sub-district, Sangihe Regency, North Sulawesi.Keywords:  fonotaktik, bahasa Gorom, dialektologis